An adjustable bio-sealing method for rock fracture leakage mitigation - Zhihao Dong; Xiaohua Pan; Chaosheng Tang; Chao Lv; Bin Shi (Journal of Rock Mechanics and Geotechnical Engineering)
This study proposed a repeated adjustable mixture injection strategy (RAM) based microbial induced carbonate precipitation (MICP) for efficient mitigation of rock fracture leakage. Granite fractures with small apertures were investigated, and bio-sealing experiments were conducted using five different cementation solution (CS) concentrations (0.25−2 M). The results showed that the RAM-based bio-sealing method can seal and bond the small aperture rock fractures with high efficiency and uniform precipitation by adjusting the CS concentration. The RAM-based bio-sealing mechanism is attributed to the following four stages: (1) fixation of bacterial flocs onto the fracture surfaces, (2) precipitation of CaCO3 onto the fracture surfaces, (3) growth of pre-precipitated CaCO3 and adhesion of new-suspended CaCO3, and (4) bridging and clogging processes. The optimal CS concentration of 1 M resulted in a fracture filling rate up to 85%, a transmissivity reduction of 4 orders of magnitude, and a shear strength ranging from 512 kPa to 688 kPa. The bio-sealing effect was found to be influenced by the CS concentration on bacterial attachment, calcium carbonate yield and calcium carbonate bulk density. The CS concentration of 1 M promoted bacterial attachment, and increased calcium carbonate yield as well as calcium carbonate bulk density, while concentrations above 1 M had the opposite effect. The bulk density of calcium carbonate played a crucial role in the sealing and bonding performance of bio-sealed fractures, particularly at comparable filling ratios and bridging areas. The bulk density was regulated by the size of calcium carbonate crystals and was determined by Ca2+ concentration in the CS. This study provides valuable insights into the RAM-based bio-sealing method, highlighting its potential for efficient rock fracture leakage mitigation through precise control of CS concentration and understanding the underlying mechanisms.